Confocal LASER endomicroscopy in Niemann–Pick disease type B. Issue 2 (4th February 2021) - Villeneuve, Thomas; Guibert, Nicolas; Collot, Samia; Fajadet, Pierre; Colombat, Magali; Courtade-Saïdi, Monique; Levade, Thierry; Didier, Alain; Prévot, Grégoire
A 41-year-old female was referred to our institution for a recent worsening of chronic cough and dyspnoea that had slowly increased over the past 6 years. She had never smoked, had no notable medical history and was not under any medication. She had two healthy children and no past family history. In 1999, some initial pulmonary function tests (PFTs) were performed in another centre to explore her chronic cough, showing a subnormal forced vital capacity (2.64 L, 95% of predicted) and diffusing capacity of the lung for carbon monoxide ( D LCO ; 90% of predicted). Chest computed tomography (CT) showed an interstitial lung disease (ILD) with interlobular septa thickening in the upper lobes associated with ground glass opacities (figure 1a). No definitive diagnosis was made and the patient was lost to follow-up. This study presents the very first pCLE images of Niemann–Pick type B disease. This minimally invasive approach, at the crossroads between imaging and histology, may represent a valuable tool in the differential diagnosis of ILDs, including NPB. https://bit.ly/2D5Bfju